Secondary interactions arrest the hemiaminal intermediate to invert the modus operandi of schiff base reaction: a route to benzoxazinones - Patel, Ketan; Deshmukh, Satej S.; Bodkhe, Dnyaneshwar; Mane, Manoj; Vanka, Kumar; Shinde, Dinesh; Rajamohanan, Pattuparambil R.; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Chikkali, Samir H. (Journal of Organic Chemistry, 2017)
Discovered by Hugo Schiff, condensation between amine and aldehyde represents one of the most ubiquitous reactions in chemistry. This classical reaction is widely used to manufacture pharmaceuticals and fine chemicals. However, the rapid and reversible formation of Schiff base prohibits formation of alternative products, of which benzoxazinones are an important class. Therefore, manipulating the reactivity of two partners to invert the course of this reaction is an elusive target. Presented here is a synthetic strategy that regulates the sequence of Schiff base reaction via weak secondary interactions. Guided by the computational models, reaction between 2,3,4,5,6-pentafluoro-benzaldehyde with 2-amino-6methylbenzoic acid revealed quantitative (99%) formation of 5-methyl-2-(perfluoropheny01,2-dihydro-4H-benzo[d][1,3]oxazin-4-one (15). Electron donating and electron withdrawing ortho-substituents on 2-aminobenzoic acid resulted in the production of benzoxazinones 936. The mode of action was tracked using low temperature NMR, IN vis spectroscopy, and isotopic (O-18) labeling experiments. These spectroscopic mechanistic investigations revealed that the hemiaminal intermediate is arrested by the hydrogen-bonding motif to yield benzoxazinone. Thus, the mechanistic investigations and DFT calculations categorically rule out the possibility of in situ imine formation followed by ring-closing, but support instead hydrogen-bond assisted ring-closing to prodrugs. This unprecedented reaction represents an interesting and competitive alternative to metal catalyzed and classical methods of preparing benzoxazinone.

Self-assembly of P-chiral supramolecular phosphines on rhodium and direct evidence for Rh-catalyst-substrate interactions - Koshti, Vijay S.; Sen, Anirban; Shinde, Dinesh; Chikkali, Samir H. (Dalton Transactions, 2017)
Supramolecular phosphine-derived catalysts are known to provide high enantioselectivity in asymmetric transformations such as hydrogenation, but direct evidence unravelling the role of secondary interactions is largely missing. As a representative case study, the role of hydrogen bonding in asymmetric hydrogenation catalysed by p-chiral supramolecular phosphines is investigated. To establish the nature of hydrogen bonding in the self-assembled Rh-complex, NMR experiments were performed at different concentrations and temperatures. It was found that with increasing concentration of 1-(3-(phenyl(o-tolyl)phosphanyl) phenyl) urea ligand (L1), the NH and NH2 peaks shift downfield. This indicated the presence of intermolecular hydrogen bonding in L1. This observation was further supported by variable temperature NMR experiments wherein, with decreasing temperature, the NH and NH2 resonances of L1 shifted downfield. The downfield shift once again suggests the existence of intermolecular hydrogen bonding in L1. In contrast, the chemical shift of NH and NH2 signals did not significantly change with increasing concentration of the self-assembled Rh-complex (C1). This observation suggested the existence of intramolecular hydrogen bonding in the self-assembled complex. The concentration experiment was further corroborated by variable temperature NMR experiments. No change in the chemical shift of NH2 resonance could be detected with decreasing temperature, which corroborates the existence of intramolecular hydrogen bonding in C1. In a stoichiometric experiment, C1 was treated with hydrogenation substrate N-acetyldehydrophenylalanine (S2) and the proton NMR was recorded. The NH2 protons of the selfassembled Rh-complex were found to shift downfield, as compared to untreated parent C1. These observations indicated that there is a hydrogen bonding interaction between the Rh-complex and the substrate. To further attest this hypothesis, NH and NH2 groups were exchanged with ND and ND2 groups, respectively, and a self-assembled Rh-complex was prepared using the deuterated supramolecular phosphine ligand L1.D. When the deuterated Rh-complex (C1.D) was treated with substrate S2, the ND and ND2 resonances were found to shift downfield. Thus, the labelling experiment further authenticated the existence of catalyst-substrate interactions. The presence of this catalyst-substrate interaction could be one of the parameters that leads to high enantiomeric excess in the asymmetric hydrogenation reaction of S2.